Tracing Transitions in the Development of Nepali Paintings - Sharma, Yam Prasad (Tribhuvan University Journal, 2023)
This article traces the transitions on the process of the development of Nepali paintings. From early period to present time, many trends of paintings have appeared, disappeared and modified. The evolution and connection of these trends, techniques and forms have been presented chronologically. The genres of Nepali paintings like manuscript illumination, paubha, patachitra, portrait, landscape, expressive works and abstract arts use different techniques and forms to explore different contents. Shift from two dimensional forms to three dimensional forms, mysticism to realism, religious to secular, realistic to expressive, expressive to abstract, and objective to subjective are the major transitions in the history of Nepali paintings. The article compares and contrasts various trends and techniques of the paintings. This research is qualitative, for the conclusion has been drawn based on the interpretation of artworks, and the interpretation of the paintings can be multiple depending on the viewers’ perspective.